The Influence of Work Environment and Human Capital on Employee Performance - Nurlia L. Suhardi; Lindanur Sipatu; Rosida Adam; Andi Indriani Ibrahim; Wisra (Al-Qalam Institue, 2026)
This study aims to examine the influence of the work environment and human capital on employee performance. The research employed a quantitative approach using a survey method. Data were collected through structured questionnaires that had been tested for validity and reliability. The sampling technique used was saturated sampling, involving 47 respondents. The data were analyzed using multiple linear regression to determine both simultaneous and partial effects of the independent variables on employee performance. The results indicate that the work environment and human capital simultaneously have a significant effect on employee performance. Partially, both the work environment and human capital individually show a significant positive effect on employee performance. The coefficient of determination reveals that 75.6% of the variation in employee performance is explained by the work environment and human capital, while the remaining 24.4% is influenced by other factors not examined in this study. The findings imply that organizations should prioritize creating a supportive work environment and strengthening human capital development to enhance employee performance. Strategic policies related to workplace conditions and employee competencies are essential to achieve optimal organizational outcomes.